Saron Music Transcription Based on Rhythmic Information using HMM on Gamelan Orchestra - Yoyon K Suprapto; Yosefine Triwidyastuti (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
Nowadays, eastern music exploration is needed to raise his popularity that has been abandoned by the people, especially the younger generation. Onset detection in Gamelan music signals are needed to help beginners follow the beats and the notation. We propose a Hidden Markov Model (HMM) method for detecting the onset of each event in the saron sound. F-measure of average the onset detection was analyzed to generate notations. The experiment demonstrates 97.83% F-measure of music transcription.